Contextual factors associated with depression among Northern and Indigenous adolescents in the Northwest Territories, Canada. (24th June 2021) - Logie, Carmen H.; Lys, Candice L.; Sokolovic, Nina; Mackay, Kayley Inuksuk; Donkers, Holly; Kanbari, Amanda; Pooyak, Sherri; Loppie, Charlotte
Abstract: Background: Persons in Arctic regions disproportionately experience depression. Knowledge gaps remain regarding factors associated with depression among adolescents in the Northwest Territories (NWT), Canada, where child and adolescent mental health hospitalizations are nearly 2.5 times the national rate. This study assesses correlates of depression among adolescents in the NWT. Methods: We conducted a cross-sectional survey with adolescents aged 13–18 in 17 NWT communities. We assessed associations between socio-demographic characteristics, dating violence, food insecurity and depression, measured with the 9-item Patient Health Questionnaire. We conducted ordered logistic regressions to assess associations with no, mild, or moderate/severe depression scores. Results: Participants ( n = 399; mean age: 14.3, s.d. : 1.3) were mostly Indigenous (79%) and 45% reported food insecurity. Nearly half (47%) reported minimal/no depression symptoms, 25% mild symptoms and 28% moderate/severe symptoms. In multivariate analyses, participants who were cisgender women compared to other genders, sexually diverse v . heterosexual, and food insecure had double the odds of more severe depression symptoms. Among those dating, dating violence was associated with double the odds of moderate/severe depression symptoms. Conclusions: Findings support tailored interventions to address material (food insecurity), relational (dating violence) and symbolic (gender and sexual orientation norms) contextual factors associated with depression among adolescents in the NWT.